1992
DOI: 10.1104/pp.98.4.1270
|View full text |Cite
|
Sign up to set email alerts
|

Ethrel (Ethylene Releaser)-Induced Increases in the Adenylate Pool and Transtonoplast ΔpH within Hevea Latex Cells

Abstract: The treatment of rubber tree (Hevea brasiliensis) bark with chloro-2-ethyl phosphonic acid (ethrel), an ethylene-releasing chemical, induced, after a lag period of 13 to 21 hours, a marked increase in the total adenine nucleotides (essentially ATP and ADP) of latex cells. This rise in the latex adenylate pool was concomitant with a marked decrease in the [ATP]/[ADP] ratio without significant changes in the adenylate energy charge. The apparent equilibrium constant for the adenylate kinase, which appeared to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 10 publications
2
28
0
1
Order By: Relevance
“…Ethylene treatment triggers a number of stimulated downstream biochemical cascades in relation to latex production: sugar loading and its catabolism 9,36,39,40 , water uptake 41 , energy availability 42 , cytosolic alkalinization 42 , nitrogen assimilation 43 and defence responses 44 . Many genes implicated in these events were among the DEGs identified in this study (Supplementary Tables 22 and 23), but not the rubber biosynthesis genes, which is consistent with the previous proposition that ethylene has little direct effect on genes in rubber biosynthesis 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Ethylene treatment triggers a number of stimulated downstream biochemical cascades in relation to latex production: sugar loading and its catabolism 9,36,39,40 , water uptake 41 , energy availability 42 , cytosolic alkalinization 42 , nitrogen assimilation 43 and defence responses 44 . Many genes implicated in these events were among the DEGs identified in this study (Supplementary Tables 22 and 23), but not the rubber biosynthesis genes, which is consistent with the previous proposition that ethylene has little direct effect on genes in rubber biosynthesis 45 .…”
Section: Resultsmentioning
confidence: 99%
“…ATP availability may therefore also play a role in regulating enzymatic activity. After ethylene stimulation, the cytosolic ATP content can reach 1.2 to 1.8 mM (Amalou et al, 1992). This would seem to induce increased PRPP synthesis, thereby enabling increased synthesis of the purine and pyrimidine nucleotides required for latex regeneration (d'Auzac et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, pH has been reported to finely tune aquaporin activity through the protonation of some of their His residues by cytosolic H + , inducing their gating (Chaumont et al, 2005;Fischer and Kaldenhoff, 2008;Verdoucq et al, 2008). Bark treatments with synthetic auxins (Tupy, 1973) as well as with Ethrel (Coupé et al, 1977;BzrozowskaHanower et al, 1979;Amalou et al, 1992) have been shown to induce marked alkalinization of the latex cell cytosol, which should help increase laticifer PIP2 activity.…”
Section: Differential Aquaporin Expression May Control Turgor Pressurmentioning
confidence: 99%